Shooting iron - Johnstone, William W.; Johnstone, J. A. (Johnstone, William W. Devil's Gulch western, 2023)
When Joe Mullen escapes his prison wagon and comes for him, making the streets of his town run red with blood, Devil's Gulch sheriff John Holt, a hardcase lawman and legendary gunslinger, vows to take the corrupt rancher down despite the odds not being in his favor.